Racemic DNA Crystallography1. Issue 52 (30th October 2014) - Mandal, Pradeep K.; Collie, Gavin W.; Kauffmann, Brice; Huc, Ivan
Abstract Racemates increase the chances of crystallization by allowing molecular contacts to be formed in a greater number of ways. With the advent of protein synthesis, the production of protein racemates and racemic‐protein crystallography are now possible. Curiously, racemic DNA crystallography had not been investigated despite the commercial availability of L‐ and D‐deoxyribo‐oligonucleotides. Here, we report a study into racemic DNA crystallography showing the strong propensity of racemic DNA mixtures to form racemic crystals. We describe racemic crystal structures of various DNA sequences and folded conformations, including duplexes, quadruplexes, and a four‐way junction, showing that the advantages of racemic crystallography should extend to DNA.